Damage to yam (Dioscorea spp.) by rootknot nematode (Meloidogyne spp.) under field and storage conditions in Uganda - Mudiope, J.; Coyne, Danny L.; Adipala, E.; Talwana, Herbert A.L. (2012)
Although root-knot nematodes (Meloidogyne spp.) are a widely distributed pest of yam (Dioscorea spp.), the level of damage the yams incur, either alone or in association with other plant-parasitic nematodes is largely undetermined. The current study assessed the damage Meloidogyne spp. caused in the field and during storage, following inoculation onto clean seed material and also to yam planted into infested fields. In general, Meloidogyne spp. caused little galling to roots and tubers, and limited reduction in plant growth and yield. Of three species tested, D. rotundata was the most susceptible and most heavily affected by Meloidogyne spp. infection, D. alata was the least affected, and D. cayenensis was intermediately affected yam species. Meloidogyne spp. infection of tubers significantly exacerbated yam tuber weight loss during storage, particularly during the first 2 months, and moreover reduced and delayed tuber sprouting. Farmers need to select tubers free of Meloidogyne spp. symptoms prior to storage to reduce losses from tuber deterioration, and while selecting planting material for the succeeding season.